Integration of Arts Learning in the Pancasila Student Profile Project at Madrasah Ibtidaiyah Model Panyabungan Mandailing Natal - Ammi Thoibah Nst; Vega Bintang Rizky; Namiroh Lubis; Asrin Nasution (ARZUSIN, 2025)
This study is motivated by the limited empirical analysis of how art learning is integrated into the Pancasila Student Profile Strengthening Project (Proyek Penguatan Profil Pelajar Pancasila/P5) in elementary schools as a strategy for character education within the Merdeka Curriculum. The research aims to describe the integration of art learning into P5 implementation in order to foster key dimensions of the Pancasila Student Profile among elementary students. Using a qualitative case study approach, the study involves classroom teachers, art and culture teachers, and fourth- to fifth-grade students at Madrasah Ibtidaiyah Model Panyambungan in Mandailing Natal Regency, with data collected through observation, in-depth interviews, and analysis of project-based art activity documents. The findings indicate that art learning functions as an effective medium for cultivating cooperation, creativity, and critical thinking, as evidenced by activities such as mural drawing, thematic drama, and collaborative music that enhance students’ active participation and creative expression in an enjoyable learning environment. The study concludes that integrating art learning into P5 is highly relevant for shaping Pancasila student character in the digital era and implies the need for systematic teacher training to design more structured, contextual, and character-oriented P5 implementation in elementary schools.